2017
DOI: 10.1159/000477733
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Autoimmune Myasthenia Gravis in a Health Maintenance Organization in Buenos Aires, Argentina

Abstract: Background: Different epidemiological studies, especially in Europe, have estimated the incidence density of myasthenia gravis (MG) to range between 1.7 and 21.3/1,000,000/person-year; however, data from regions such as Latin America are scarce. This study is aimed at estimating the incidence and prevalence of acquired MG in Buenos Aires, Argentina. Methods: The study population comprised of affiliates of the Italian Hospital Medical Care Program, a prepaid health maintenance organization located in Buenos Air… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 18 publications
1
10
0
5
Order By: Relevance
“…These data may further support the observation of a general increase in the incidence of autoimmune diseases in general and the high rate of autoimmune diseases in Israel in particular. As the pathogenesis of MG is thought to be influenced by a combination of genetic and environmental factors, 43‐45 one may speculate that our findings, also observed in other studies, 16‐18,22‐23,32‐36,38,46‐50 can be attributed to changes in environmental factors such as exposure to infective pathogens, diet, and contact with ecological compounds.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These data may further support the observation of a general increase in the incidence of autoimmune diseases in general and the high rate of autoimmune diseases in Israel in particular. As the pathogenesis of MG is thought to be influenced by a combination of genetic and environmental factors, 43‐45 one may speculate that our findings, also observed in other studies, 16‐18,22‐23,32‐36,38,46‐50 can be attributed to changes in environmental factors such as exposure to infective pathogens, diet, and contact with ecological compounds.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, the occurrence of MG is influenced by sex and age: Women are affected nearly three times more than men during early adulthood (<40 years), whereas incidence is roughly equal after this age 13,14 . Also, in the last decades, MG incidence in the elderly has increased, probably due to increased awareness and increased longevity 10,15‐24 …”
Section: Introductionmentioning
confidence: 99%
“…Two population-based studies from Korea showed a prevalence of 9.67–10.42 per 100,000 people in 2010, which increased to 12.99 per 100,000 in 2014 [ 17 , 18 ]. On the other hand, a smaller study using records of a hospital-based Health Maintenance Organization estimated an incidence of MG at 38.8 per 1,000,000 person-years for the Argentinian population [ 19 ]. Different study methodologies, including diagnostic criteria and other sources of bias, such as the small size of the study population and the underestimation of patients with milder disease, likely play a factor in the significant variability of incidence rates over time and across different geographical regions.…”
Section: Epidemiologymentioning
confidence: 99%
“…3 ). The highest prevalence was reported in Salvado et al [ 61 ]; 3463 per 100,000 population and the lowest prevalence Bettini et al [ 58 ]; 0.006 people reported per 100,000 population.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…In the current systematic review and meta-analysis study, the overall prevalence of MG in the world; 12.4 people per 100,000 population were obtained. Most prevalent in Salvado et al [ 61 ]; 3463 per 100,000 population and the lowest prevalence Bettini et al [ 58 ]; 0.006 people per 100,000 population reported.…”
Section: Discussionmentioning
confidence: 99%